PERBANDINGAN KONSTITUSI TENTANG PEMBATASAN MASA PERIODE JABATAN PRESIDEN DI INDONESIA DAN FILIPINA - SINURAT, ARGA SANDYA RAJA; Haryono, Dodi; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The president is the head of government (chief of executive), but also the head of state (chief of state).The term of office of the president in various countries is different. The term of office of the president inIndonesia in one period of five years can be elected twice based on Article 7 of the 1945 Constitution, whilein the Philippines the term of office of the president can only be elected once in a year. one period for six yearsbased on the Philippine Constitution Chapter 7 Article 4. Therefore, this research aims to find out and comparethe two countries in terms of similarities/differences, advantages/disadvantages, and the urgency ofcomparison to strengthen regulations limiting the period of presidential office in Indonesia and thePhilippines.This type of research can be classified as a normative research type. The research focuses on examiningthe comparison of term limits for the presidents of Indonesia and the Philippines. The data sources used aresecondary data in the form of primary legal materials, namely the 1945 Constitution and the PhilippineConstitution, secondary legal materials, namely documents and journals, and tertiary legal materials, namelylegal dictionaries. The data collection technique in this research is the literature review method, usingDescriptive analysis describes, describes and compares the Indonesian and Philippine constitutions regardingpresidential term limits.Limiting the presidential term of office for Indonesia and the Philippines has similarities/differences,advantages/disadvantages, and the urgency of strengthening the implementation of presidential termregulations. The similarities/differences are that the countries have the same principle of Trias Politica(Division of power) while the differences in this case provide for re-nomination. The advantages guaranteethe creation of democratic politics, economic growth, lack of potential for corruption while the shortcomingsalso hinder the regeneration of new leaders from the executive branch. The urgency is to limit the presidentialperiod to prevent continued political instability. That in this case the researcher provides suggestions, it ishoped that policy makers will make legal politics related to the rules for limiting the term of office of thepresident by changing the provisions governing the term of office of the president as well as communityinvolvement, political style, and modernity by giving the term of office of the president to one term withprovisions as long as one period of six years.Keywords : Constitution - Period - Limitations